Research Note: The Influence of Micro-oxygenation on the Long-term Ageing Ability of Pinot noir Wine - Yang, Yi; Deed, Rebecca C.; Araujo, Leandro D.; Kilmartin, Paul A. (South African Journal of Enology and Viticulture, 2022)
In this study, Pinot noir wines were bottle aged for 12 and 18 months after micro-oxygenation (MOX) applied before or after malolactic fermentation (MLF) at two doses (10.8 and 52.4 mg/L/month). After ageing, a greater decrease in the total SO2 concentration was found in wines with the higher MOX dosage, demonstrating a long-term impact of higher oxygen exposure on wines’ SO2 requirement. Meanwhile, a negative impact of MOX on wine colour development occurred over time, resulting in a large loss of colour measures (i.e., 420 nm for brown hues, 520 nm for red colour, SO2 resistant pigments, and colour intensity), which was greater with the early oxygen exposure. This was linked to a significantly lower content of large polymeric pigments in MOX treatments. Tannin concentration was, in the end, not affected by the MOX treatments. However, regarding tannin composition, considerably higher (-)-epicatechin extension units but much lower (-)-epicatechin terminal units were found with MOX treatments. In addition, a significant reduction of tannin trihydroxylation (%Tri-OH) but a higher galloylation (%Galloyl) and mean degree of tannin polymerisation (mDP) remained in wines with MOX, indicating a long-term negative influence on astringency intensity.